High-temperature-resistant and glass-corrosion-resistant alloy, preparation method and application thereof
By preparing high-temperature resistant and glass corrosion-resistant alloys with specific compositions, the failure problem of electrode materials for nuclear waste glass solidification furnaces under high temperature and corrosive environments has been solved, resulting in a longer service life and lower radioactive waste generation.
Patent Information
- Application Number
- CN202511332045.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-18
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-09-18
AI Technical Summary
Existing electrode materials for nuclear waste glass solidification furnaces are prone to failure under high temperature and corrosive environments, resulting in insufficient lifespan. In particular, the Cr2O3 film formed on the surface of nickel-based Inconel 690 alloy is loose, the oxide film has poor adhesion to the substrate, and the glass corrosion rate is high.
A high-temperature resistant and glass corrosion resistant alloy containing specific alloying elements such as Cr, Al, Ti, Y and Ni is prepared through processes such as vacuum induction melting, electroslag remelting and high-temperature forging to form a dense oxide film to improve oxidation resistance and glass corrosion resistance.
This improved the alloy's high-temperature resistance, glass corrosion resistance, and oxidation resistance, extended the service life of nuclear waste glass solidification furnaces, and reduced the generation of secondary radioactive waste.
Smart Images

Figure CN120830029B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of corrosion-resistant high-temperature alloys, and more specifically, relates to a high-temperature resistant and glass corrosion-resistant alloy, its preparation method, and its application. Background Technology
[0002] With the rapid development of the nuclear industry, the amount of highly hazardous high-level radioactive waste (hereinafter referred to as high-level waste or high-level liquid waste) generated in the reprocessing of nuclear fuel cycle and the direct disposal of spent fuel is increasing rapidly, growing at a rate of 600 tons per year, posing a serious problem of insufficient storage space. Due to its high radioactivity levels, long half-life, and high biotoxicity, the treatment and disposal of high-level waste has become a global concern. In response to this problem, a major nuclear waste reprocessing project has been launched, employing the "vitrification-geological disposal" process to treat high-level waste. As the most effective and mature high-level liquid waste treatment technology in the world, vitrification has received significant attention both domestically and internationally. Electrodes are key components of the vitrification furnace. During service, they are subjected to harsh environments such as high temperatures, corrosion, and irradiation, leading to oxidation, molten glass corrosion, and high-temperature thermal fatigue damage, causing electrode failure and becoming a major factor limiting the service life of the vitrification furnace.
[0003] Currently, the electrode materials used in glass curing furnaces are mainly molybdenum and nickel-based Inconel 690 alloys. Molybdenum has a high melting point (2620℃), good electrical conductivity, low contact resistance, strong resistance to glass melt erosion, and high current density (2A / cm). 2 Molybdenum is widely used in civilian glass melting furnaces. However, metallic molybdenum begins to oxidize rapidly at temperatures above 382°C. Therefore, molybdenum electrodes require cooling water jackets to prevent oxidation, making them difficult to control and highly dangerous when used as electrodes in nuclear waste glass solidification furnaces. They are only used in Russian Joule-heated ceramic furnaces. Nickel-based Inconel 690 material has excellent comprehensive properties such as oxidation resistance, conductivity, and glass corrosion resistance, and is used in electrodes for nuclear waste glass solidification furnaces in the United States, Germany, and Japan.
[0004] Although the nickel-based Inconel 690 alloy possesses excellent comprehensive mechanical properties, corrosion resistance, machinability, and weldability, and is used abroad to manufacture furnace electrodes, the Cr2O3 film formed on its surface in the service environment is loose and not dense. The oxide film has poor adhesion to the substrate and is prone to detachment, resulting in a still relatively high glass corrosion rate and insufficient lifespan for glass hardening furnaces. Therefore, there is an urgent need for a new high-temperature resistant and glass corrosion-resistant alloy and its preparation method, and for using this alloy to manufacture electrodes for nuclear waste glass hardening furnaces. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing technologies by providing a high-temperature resistant and glass corrosion-resistant alloy, its preparation method, and its applications. The high-temperature resistant and glass corrosion-resistant alloy of this invention exhibits excellent high-temperature resistance, glass corrosion resistance, and oxidation resistance.
[0006] To achieve the above objectives, a first aspect of the present invention provides a high-temperature resistant and glass corrosion-resistant alloy, wherein, based on the total weight of the alloy, the alloy comprises: C 0-0.03%, Mn 0-0.4%, Si 0-0.4%, Cr 28-31%, Fe 8-11%, Al 0.001-0.5%, Ti 0-0.5%, Y 0.001-0.03%, S 0.002%, P 0.002%, impurity elements <0.1%, the remainder is Ni.
[0007] In this invention, the impurity elements include oxygen and nitrogen.
[0008] According to the present invention, preferably, the alloy comprises, by total weight: C 0.005-0.02%, Mn 0.2-0.4%, Si 0.2-0.4%, Cr 28-31%, Fe 8-11%, Al 0.05-0.40%, Ti 0.01-0.3%, Y 0.001-0.02%, S 0.0015%, P 0.0015%, impurity elements <0.05%, the remainder is Ni.
[0009] More preferably, based on the total weight of the alloy, the alloy comprises: C 0.008-0.015%, Mn 0.2-0.35%, Si 0.2-0.35%, Cr 28-31%, Fe 8-11%, Al 0.1-0.3%, Ti 0.05-0.3%, Y 0.01-0.02%, S 0.0015%, P 0.0015%, impurity elements <0.05%, the remainder is Ni.
[0010] According to the present invention, preferably, the Ni content is ≥ 58% based on the total weight of the alloy.
[0011] A second aspect of the present invention provides a method for preparing the aforementioned high-temperature resistant and glass corrosion-resistant alloy, the method comprising the following steps:
[0012] S1: The raw material of element C, metal Ni, metal Cr and metal Fe are mixed and vacuum induction melting and refining are carried out to obtain refined material; after the refining is completed, the refined material is mixed and melted with metal Al, metal Ti, metal Y, metal Mn and elemental Si under protective gas, and then cast to obtain master alloy ingot.
[0013] S2: Electroslag remelting of the master alloy ingot under a protective gas to obtain an electroslag remelted ingot;
[0014] S3: The electroslag remelting ingot is homogenized to obtain a homogenized ingot;
[0015] S4: The homogenized ingot is subjected to forging blanking and forging processing to obtain a forging;
[0016] S5: The forging is subjected to solution treatment and aging treatment in sequence to obtain the high temperature resistant and glass corrosion resistant alloy.
[0017] In this invention, the protective gas in step S1 is high-purity argon at 0.4 atm. As a preferred embodiment, step S1 is as follows: First, preheating with low power (5-20 kW) removes moisture and impurities from the raw materials containing C, Ni, Cr, and Fe. Then, the power is increased to high power (50-80 kW) to rapidly raise the temperature to 1500℃-1600℃ for vacuum induction melting. Next, the temperature is lowered to 1450℃-1500℃ for refining for 10-20 minutes. Then, high-purity argon at 0.4 atm is introduced into the vacuum induction melting furnace. Afterward, high-purity Al, Ti, Y, Mn, and Si are added from the hopper, and the temperature is immediately and rapidly raised to 1500℃-1600℃, held for 3-6 minutes for mixing and melting. Finally, the temperature is lowered to 1450℃-1500℃ for casting to obtain the master alloy ingot.
[0018] According to the present invention, preferably, the raw material of element C is at least one of graphite rods, graphite blocks, and graphite powder.
[0019] According to the present invention, preferably, the operating conditions for vacuum induction melting include: melting temperature of 1500-1600℃ and vacuum degree of 0.1-1Pa.
[0020] According to the present invention, preferably, the refining temperature is 1450-1500℃ and the refining time is 10-20 min.
[0021] According to the present invention, preferably, the mixing and melting temperature is 1500-1600℃, and the mixing and melting time is 3-6 min.
[0022] According to the present invention, preferably, the pouring temperature is 1450-1500°C.
[0023] In this invention, the protective gas in step S2 is nitrogen. As a preferred embodiment, step S2 is as follows: the master alloy ingot prepared in step S1 is peeled to remove the oxide layer, then welded to a dummy electrode in a nitrogen-protected electroslag remelting furnace, and subsequently connected to the positive electrode of an electroslag remelting device; then, electroslag is spread for arc initiation and melting, using a hexa-element slag system with the following composition: Al2O3 20-25%, CaO 20-30%, TiO2 4-6%, MgO 1-4%, CaF2 40-60%, SiO2 0-1%; after the electroslag is completely melted, the current is gradually increased for electrode electroslag remelting until the electrode is melted down to approximately 100mm, then the current is gradually reduced to a filling current for filling and shrinkage, resulting in an electroslag remelted ingot; nitrogen is introduced throughout the melting process for gas protection.
[0024] According to the present invention, preferably, the electroslag remelting includes spreading electro-slag and arc ignition smelting, and the electro-slag comprises, by weight, the electro-slag: Al2O3 20-25%, CaO 20-30%, TiO2 4-6%, MgO 1-4%, CaF2 40-60%, and SiO2 0-1%.
[0025] In this invention, before the homogenization process, the head and tail of the electroslag remelted ingot need to be removed and the surface oxide layer needs to be removed before it is placed in a high-temperature resistance furnace for homogenization.
[0026] According to the present invention, preferably, the homogenization treatment temperature is 1150-1200℃, and the homogenization treatment time (i.e., the heat preservation time) is >6 hours.
[0027] In this invention, after the homogenization treatment is completed, the homogenized alloy is subjected to three-stage forging and three-stage drawing after exiting the high-temperature resistance furnace. The final forging temperature of the forging is not lower than 950°C. Then, the forging after the forging is further forged. The initial forging temperature and the final forging temperature of the forging process are the same as those of the forging process, and forgings of suitable size are produced.
[0028] According to the present invention, preferably, the final forging temperature of the forging blank and the final forging temperature of the forging process are each independently ≥950°C.
[0029] According to the present invention, preferably, the forging ratio of the forging process is 2-5.
[0030] According to the present invention, preferably, the solution treatment temperature is 1050-1090°C and the solution treatment time is 10-30 min.
[0031] According to the present invention, preferably, the aging treatment temperature is 700-720°C and the aging treatment time is 5-20 hours.
[0032] The third aspect of this invention provides the application of the high-temperature resistant and glass corrosion resistant alloy described above or the high-temperature resistant and glass corrosion resistant alloy prepared by the preparation method described above in the preparation of electrodes for nuclear waste glass solidification furnaces.
[0033] The design concept for determining the alloy composition in this invention is:
[0034] (1) Fe: increases lattice mismatch, hinders dislocation movement, and at the same time reduces stacking fault energy, thereby increasing alloy strength;
[0035] (2) Al: an element that forms internal oxidation products and hinders the formation of Cr. 3+ Ion diffusion reduces the formation of pores, improves the anti-scraping ability of the oxide film, and enhances the alloy's resistance to glass corrosion and oxidation.
[0036] (3) Ti: Trace amounts of Ti promote the formation of Al2O3, which helps to improve the resistance to high-temperature oxidation;
[0037] (4) Cr: By adding Cr element to form a Cr2O3 oxide film on the surface, the oxidation resistance of the alloy is improved and the diffusion of O element into the alloy is hindered.
[0038] (5) C: Forms carbides, improving the mechanical properties of the alloy, but promotes the growth of Cr. 3+ Ion diffusion promotes the formation of pores and reduces the alloy's resistance to glass corrosion; therefore, the amount added must be controlled.
[0039] (6) Mn: a solid solution element that improves the alloy’s plasticity, toughness, and corrosion resistance;
[0040] (7) Si: When combined with the Cr2O3 oxide film, it can improve the oxidation resistance of the alloy;
[0041] (8) Y: Purify the grain boundaries of the alloy and improve the corrosion resistance of the grain boundaries.
[0042] The beneficial effects of the technical solution of the present invention are as follows:
[0043] 1. This invention first employs a dual-smelting technology of purified vacuum induction melting and electroslag remelting to prepare alloy ingots, which are then forged at high temperatures to obtain high-quality forgings. The high-temperature resistant and glass corrosion-resistant alloy of this invention possesses excellent high-temperature resistance, glass corrosion resistance, and oxidation resistance. This high-temperature resistant and glass corrosion-resistant alloy belongs to the category of materials with high glass corrosion resistance. Using this high-temperature resistant and glass corrosion-resistant alloy to prepare electrodes for nuclear waste vitrification furnaces can improve the lifespan of high-level radioactive waste vitrification furnaces, thereby reducing secondary radioactive waste generated during the dismantling of vitrification furnaces.
[0044] 2. This invention utilizes an appropriate amount of Al element to generate internal oxidation products at grain boundaries to affect Cr. 3+The inhibition of ion diffusion reduces the formation of pores and improves the resistance of the oxide film to peeling, thereby enhancing the alloy's resistance to glass corrosion and high-temperature oxidation. Specifically, by adding trace amounts of the "active element" Al, endogenous oxidation products are generated at the alloy grain boundaries, utilizing Cr... 3+ The phenomenon that the diffusion rate of ions in oxides is two orders of magnitude smaller than that in the matrix suppresses Cr. 3+ The diffusion of ions reduces the effect of Cr 3+ The generation of numerous pores in the matrix due to ion diffusion enhances the oxide film's resistance to peeling. On the other hand, the pinning effect of endogenous oxides on the oxide film also enhances its resistance to peeling, thereby improving the alloy's resistance to glass corrosion and high-temperature oxidation.
[0045] 3. This invention purifies the alloy grain boundaries and reduces the alloy grain boundary corrosion rate by adding trace amounts of rare earth element Y. Specifically, this invention utilizes the strong affinity between rare earth atoms and impurity atoms such as sulfur, oxygen, and nitrogen at the grain boundaries. These rare earth atoms form stable compounds with high melting points and low diffusion coefficients, which are then expelled from the alloy. This prevents impurity atoms from agglomerating at the grain boundaries, purifies the alloy grain boundaries, reduces the electrochemical activity of the alloy, decreases the tendency for electrochemical corrosion at the grain boundaries, and improves the alloy's resistance to intergranular corrosion.
[0046] 4. The control of carbon (C) content in this invention plays a crucial role in balancing the alloy's resistance to glass corrosion and its mechanical properties. Reducing the C content improves the alloy's resistance to glass corrosion but reduces its mechanical properties. Specifically, by controlling the C content, this invention, on the one hand, forms fine and uniformly distributed carbide particles at the grain boundaries, acting as obstacles to dislocation movement, thereby increasing the alloy's yield strength and tensile strength. On the other hand, while ensuring the alloy's appropriate mechanical properties, it minimizes galvanic corrosion caused by the potential difference between the carbides and the matrix, thus improving the alloy's resistance to molten glass corrosion.
[0047] 5. The high glass corrosion resistance material of the present invention is obtained by melting glass at 1150℃ and 5 10 3 -9 10 3 A / m 2 Under alternating current, the corrosion rate of borosilicate glass is less than or equal to 2 mm / year.
[0048] 6. The high glass corrosion resistance material of the present invention has an oxidation resistance grade at a high temperature of 1200℃.
[0049] 7. The nickel-based superalloy obtained after aging treatment according to the present invention has a room temperature tensile strength. 580MPa, aging strength 240MPa, elongation 30%.
[0050] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0051] The above and other objects, features and advantages of the present invention will become more apparent from the more detailed description of exemplary embodiments of the invention in conjunction with the accompanying drawings.
[0052] Figure 1 This illustrates a high-temperature resistant and glass corrosion-resistant alloy provided in Embodiment 1 of the present invention, in which molten glass and 7... 10 3 A / m 2 Corrosion photographs under alternating current (taken using a scanning electron microscope).
[0053] Figure 2 The invention illustrates an alloy provided in Comparative Example 1, which is used to melt glass and 7 at 1150°C. 10 3 A / m 2 Corrosion photographs under alternating current (taken using a scanning electron microscope). Detailed Implementation
[0054] Preferred embodiments of the invention will now be described in more detail. While preferred embodiments of the invention are described below, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that the invention will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art.
[0055] In the following embodiments and comparative examples:
[0056] An alloy was prepared using 99.99 wt.% pure metal Al, 99.9 wt.% pure metal Ni, 99.9 wt.% pure metal Mn, 99.9 wt.% pure metal Cr, 99.9 wt.% pure metal Ti, 99.99 wt.% pure metal Fe, 99.3 wt.% pure elemental Si, 99.99 wt.% pure graphite rod, and 99.9 wt.% pure metal Y.
[0057] Example 1
[0058] This embodiment provides a high-temperature resistant and glass corrosion resistant alloy, which, by total weight, comprises: C 0.015%, Mn 0.32%, Si 0.36%, Cr 29.1%, Fe 9.9%, Al 0.3%, Ti 0.1%, Y 0.02%, S 0.0012%, P 0.0014%, impurity elements <0.05%, and the remainder being Ni;
[0059] The preparation method of the high-temperature resistant and glass corrosion resistant alloy includes the following steps:
[0060] S1: First, preheating with low power (15kw) removes moisture and impurities from the graphite rod, metallic Ni, metallic Cr, and metallic Fe. Then, the power is increased to high power (60kw) to rapidly raise the temperature to 1550℃ for vacuum induction melting. Next, the temperature is lowered to 1480℃ and refined for 15 minutes. Then, 0.4 atm of high-purity argon gas is introduced into the vacuum induction melting furnace. After that, high-purity Al, Ti, Y, Mn, and Si are added to the refined material from the hopper. The temperature is then immediately and rapidly raised to 1520℃ and held for 3-6 minutes for mixing and melting. Finally, the temperature is lowered to 1480℃ for casting to obtain the master alloy ingot.
[0061] Among them, since Y purifies the alloy grain boundaries, forms stable compounds with impurity elements with high melting points and low diffusion coefficients and is discharged from the alloy, the amount of Y added in the alloy preparation process should be higher than 0.02%.
[0062] S2: After removing the oxide layer from the master alloy ingot prepared in step S1, it is welded to the dummy electrode of the nitrogen-protected electroslag remelting furnace, and then connected to the positive electrode of the electroslag remelting device; then, electroslag is spread and arc-initiated for melting, using a hexa-element slag system with the following composition: Al2O3 23%, CaO 23%, TiO2 5%, MgO 3%, CaF2 45.5%, SiO2 0.5%; after the electroslag is melted, the current is gradually increased for electrode electroslag remelting until the electrode is melted down to about 100mm, then the current is gradually reduced to the filling current for filling and shrinkage, to obtain the electroslag remelted ingot; nitrogen is introduced for gas protection throughout the melting process;
[0063] S3: Cut off the head and tail of the electroslag remelting ingot obtained in step S2 and remove the surface oxide layer. Then put it into a high-temperature resistance furnace for homogenization treatment. The holding temperature is 1180℃ and the holding time is 7 hours to obtain a homogenized ingot.
[0064] S4: After homogenization, the homogenized alloy is taken out of the high-temperature resistance furnace and then subjected to three-stage forging and three-stage drawing for the blank. The final forging temperature of the blank is 1000℃. Then, the blanked forging is further forged. The initial forging temperature and the final forging temperature are the same as the blanking process. The forging is produced with a forging ratio of 3.
[0065] S5: The forging is subjected to solution treatment (solution treatment temperature 1080℃, treatment time 15min) and aging treatment (aging treatment temperature 715℃, treatment time 10h) in sequence to obtain the high temperature resistant and glass corrosion resistant alloy.
[0066] Example 2
[0067] This embodiment provides a high-temperature resistant and glass corrosion resistant alloy. The only difference between this embodiment and Embodiment 1 is that the Al content in the alloy composition is increased from 0.3% to 0.4%, while the other element compositions are the same as in Embodiment 1, with the balance being Ni.
[0068] The steps for preparing the alloy in this embodiment are exactly the same as those in Example 1.
[0069] Example 3
[0070] This embodiment provides a high-temperature resistant and glass corrosion resistant alloy. The only difference between this embodiment and embodiment 1 is that the Al content in the alloy composition is reduced from 0.3% to 0.1%, while the other elemental compositions are the same as in embodiment 1, with the balance being Ni.
[0071] The steps for preparing the alloy in this embodiment are exactly the same as those in Example 1.
[0072] Example 4
[0073] This embodiment provides a high-temperature resistant and glass corrosion resistant alloy. The only difference between this embodiment and Embodiment 1 is that the C element content in the alloy composition of this embodiment is increased from 0.015% to 0.025%, while the other element compositions are the same as in Embodiment 1, with the balance being Ni.
[0074] The steps for preparing the alloy in this embodiment are exactly the same as those in Example 1.
[0075] Example 5
[0076] This embodiment provides a high-temperature resistant and glass corrosion resistant alloy. The only difference between this embodiment and embodiment 1 is that the C element content in the alloy composition is reduced from 0.015% to 0.01%, while the other element compositions are the same as in embodiment 1, with the balance being Ni.
[0077] The steps for preparing the alloy in this embodiment are exactly the same as those in Example 1.
[0078] Example 6
[0079] This embodiment provides a high-temperature resistant and glass corrosion resistant alloy. The only difference between this embodiment and Embodiment 1 is that the Y element content in the alloy composition is reduced from 0.02% to 0.01%, while the other element compositions are the same as in Embodiment 1, with the balance being Ni.
[0080] The steps for preparing the alloy in this embodiment are exactly the same as those in Example 1.
[0081] Example 7
[0082] This embodiment provides a high-temperature resistant and glass corrosion resistant alloy. The only difference between this embodiment and Embodiment 1 is that the forging ratio in step S4 is 2.
[0083] Example 8
[0084] This embodiment provides a high-temperature resistant and glass corrosion resistant alloy. The only difference between this embodiment and Embodiment 1 is that the forging ratio in step S4 is 4.
[0085] Example 9
[0086] This embodiment provides a high-temperature resistant and glass corrosion resistant alloy. The only difference between this embodiment and Embodiment 1 is that the solution treatment temperature is 1060℃ and the treatment time is 15min.
[0087] Comparative Example 1
[0088] This comparative example provides an alloy, which differs from Example 1 only in that: the alloy composition of this comparative example has an Al content of 0%, the other element compositions are the same as those of Example 1, and the balance is Ni;
[0089] The steps for preparing this comparative alloy are exactly the same as those in Example 1.
[0090] Comparative Example 2
[0091] This comparative example provides an alloy, which differs from Example 1 only in that: the Y element content in the alloy composition of this comparative example is 0%, the other element compositions are the same as in Example 1, and the balance is Ni;
[0092] The steps for preparing this comparative alloy are exactly the same as those in Example 1.
[0093] Comparative Example 3
[0094] This comparative example provides an alloy, which differs from Example 1 only in that the C content in the alloy composition of this comparative example is increased from 0.015% to 0.035%, while the other element compositions are the same as in Example 1, with the balance being Ni;
[0095] The steps for preparing this comparative alloy are exactly the same as those in Example 1.
[0096] Test case
[0097] This test example conducted room temperature tensile property tests, oxidation resistance tests, and borosilicate glass corrosion resistance rate tests on the alloys of Examples 1-9 and Comparative Examples 1-3. The results of tensile strength, yield strength, elongation, oxidation resistance, and borosilicate glass corrosion resistance rate of the alloys of Examples 1-9 and Comparative Examples 1-3 are shown in Table 1.
[0098] in:
[0099] The room temperature tensile properties of the alloy were tested according to GB / T 228.1-2010 "Metallic materials - Tensile testing - Part 1: Test at room temperature" using an INSTRON 55822 electronic universal testing machine.
[0100] The oxidation resistance grade of the alloy at 1200℃ was tested according to GB / T13303 "Determination of oxidation resistance of steel";
[0101] The alloy melts at 1150℃, glass, and 7 10 3 A / m 2 The corrosion rate test method under alternating current is as follows:
[0102] (1) Test conditions
[0103] Test temperature: The test temperature should generally be equal to or slightly higher than the material's service temperature; the melting temperature of nuclear waste glass in the curing furnace is generally below 1150℃, therefore the test temperature is selected as 1150℃;
[0104] Experiment duration: 7 days;
[0105] Specimens: The specimens include simulated electrode specimens and control specimens. The slurry-shaped simulated electrode has a handle size of 278 mm. 8.5mm 8.4mm, paddle portion size is 76mm 76mm 8.4mm, two pieces per set, the size of the comparison plate sample is 278mm. 34mm 8.4 mm, one piece per set; the surface roughness of both types of samples is 0.8;
[0106] (2) Preparation before the experiment
[0107] Sample preparation: The sample can be marked with an electric pen. The sharp edges and burrs of the sample can be gently removed with metallographic sandpaper, and then the dimensions can be measured.
[0108] Preparation of heating furnace and temperature controller: First, clean the furnace chamber and the chromium corundum spinel composite crucible. Strictly check that there are no volatile substances at high temperatures in the furnace chamber, and that there are no acids, alkalis, salts or other contaminants. There should be no foreign objects in the crucible. Check that the temperature controller is in normal working order. For new furnaces or furnaces that have not been used for a long time, preheat the furnace at a temperature 30-50°C higher than the test temperature for a certain period of time. The uniformity of furnace temperature should be checked every three months or before each test.
[0109] (3) Vitreous preparation
[0110] The glass body is made of borosilicate glass. The glass is inspected to ensure that there are no impurities or contaminants. A certain amount of glass is weighed according to the density of the molten glass and the size of the crucible for later use.
[0111] (4) Experimental process and steps
[0112] The dimensions (width) of each sample were measured using vernier calipers. );
[0113] After the furnace temperature reaches the test temperature, maintain this temperature for 1 hour to ensure the glass in the crucible melts completely and the temperature remains uniform. Then, insert two simulated electrodes connected to the positive and negative terminals of an AC power supply into the molten glass, and apply a certain voltage between the two electrodes to achieve a temperature of 7. 10 3 A / m 2 The current density is adjusted by regulating the power of the glass heating furnace to maintain the temperature of the molten glass in the crucible at the test temperature T. 20℃; The simulated electrode was placed in molten glass, and the control sample was also placed in the molten glass at the same time to conduct a comparative experiment on the effect of the current on the corrosion resistance of the electrode material to molten borosilicate glass; In the subsequent 7 consecutive days of testing, the temperature of the molten glass was maintained at T. 20℃;
[0114] After the predetermined test time was reached, all three alloy samples were removed from the melt and quenched in deionized water. Corrosion products on the sample surface were removed by chemical method, and the samples were rinsed with deionized water and alcohol in sequence, and then dried with a hair dryer.
[0115] To calculate the dimensional corrosion rate, the dimensions (width) of the dried sample were measured using vernier calipers. ), calculate the dimensional corrosion rate K :
[0116] ,in:
[0117] —— The width of the sample before the test, in mm;
[0118] —— The width of the test specimen after the test, in mm;
[0119] —— t The test duration is y (years).
[0120] Table 1
[0121]
[0122] As shown in Table 1:
[0123] A comparison of the data from Examples 1, 2, and 3 in Table 1 shows that within the Al content range of 0.1-0.4%, the room temperature tensile strength of the alloy slightly increases with increasing Al content. This is due to the solid solution strengthening effect of Al. However, both excessively high and insufficient Al content will deteriorate the alloy's resistance to glass corrosion. This is because insufficient Al results in fewer endogenous oxidation products at the grain boundaries, which is detrimental to Cr. 3+ Al has a weak inhibitory effect on ion diffusion; while excessive Al will form coarse oxides in the alloy matrix, which will damage the bonding force between the oxide film and the matrix, leading to a decrease in glass corrosion resistance. Only an appropriate amount of Al forms a dispersed oxide at the grain boundaries, reducing the corrosion caused by Cr. 3+ The proliferation of matrix pores caused by ion diffusion, such as Figure 1 As shown, a dense Cr2O3 oxide film forms on the inner surface of the alloy in the service environment, which improves the alloy's resistance to glass corrosion and oxidation.
[0124] A comparison of the data from Examples 1, 4, and 5 in Table 1 shows that within the range of C 0.01-0.03%, increasing the C content is beneficial to improving the room temperature tensile strength of the alloy. This is because as the C content increases, the amount of carbides generated in the alloy matrix increases, thus increasing the alloy strength. However, the formation of a large amount of carbides will aggravate galvanic corrosion between the alloy and the matrix, reducing the alloy's resistance to molten glass corrosion and its oxidation resistance.
[0125] As can be seen from the comparison of the data of Example 1 and Example 6 in Table 1, within the range of Y 0.01-0.03%, the effect of Y element on the room temperature tensile properties, oxidation resistance and glass corrosion resistance of the alloy is not significant.
[0126] As can be seen from the data comparison of Examples 1, 7 and 8 in Table 1, when the alloy composition remains unchanged, the room temperature tensile strength of the alloy increases with the increase of the forging ratio, but the effect on the oxidation resistance and glass corrosion resistance is not significant, indicating that the oxidation resistance and glass corrosion resistance of the alloy are more significantly affected by the alloy composition.
[0127] As can be seen from the comparison of the data of Example 1 and Example 9 in Table 1, within the range of 1050-1090℃, the change of solution temperature has no significant effect on the room temperature tensile strength, oxidation resistance and glass corrosion resistance of the alloy.
[0128] As can be seen from the comparison of the data of Example 1 and Comparative Example 1 in Table 1, trace amounts of Al have no significant effect on the room temperature tensile properties of the alloy, but significantly improve the alloy's oxidation resistance and glass corrosion resistance. The Al-free alloy of Comparative Example 1 decreased from the oxidation-resistant grade to the sub-oxidation-resistant grade at 1200℃, and its oxidation resistance at 1150℃ was significantly reduced compared to the molten glass and 7... 10 3 A / m 2 The corrosion rate increased to 4.3 mm / y under alternating current. The main reason is that, although a Cr2O3 oxide film forms on the surface of the Al-free alloy material in the service environment, the film is loose and not dense, providing weak protection to the substrate. Figure 2 As shown.
[0129] As can be seen from the comparison of the data of Example 1 and Comparative Example 2 in Table 1, trace amounts of Y have no significant effect on the room temperature tensile properties of the alloy, but they improve the alloy's oxidation resistance and glass corrosion resistance.
[0130] As can be seen from the comparison of the data of Example 1 and Comparative Example 3 in Table 1, although the excessively high C content (0.035%) is beneficial to improve the room temperature tensile strength of the alloy, it will significantly reduce the alloy's resistance to molten glass corrosion and oxidation resistance.
[0131] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A high-temperature resistant and glass corrosion resistant alloy, characterized in that, Based on the total weight of the alloy, the alloy comprises: C 0-0.03%, Mn 0-0.4%, Si 0-0.4%, Cr 28-31%, Fe 8-11%, Al 0.001-0.5%, Ti 0-0.5%, Y 0.001-0.03%, S <0.002%, P <0.002%, impurity elements <0.1%, and the remainder being Ni; The alloy was melted at 1150°C into glass and 5×10 3 -9×10 3 A / m 2 Under alternating current, the corrosion rate of borosilicate glass is less than or equal to 2 mm / year; The alloy has a room temperature tensile strength ≥580MPa, a yield strength ≥240MPa, and an elongation ≥30%.
2. The high-temperature resistant and glass corrosion-resistant alloy according to claim 1, wherein, Based on the total weight of the alloy, the alloy comprises: C 0.005-0.02%, Mn 0.2-0.4%, Si 0.2-0.4%, Cr 28-31%, Fe 8-11%, Al 0.05-0.40%, Ti 0.01-0.3%, Y 0.001-0.02%, S <0.0015%, P <0.0015%, impurity elements <0.05%, and the remainder being Ni.
3. The high-temperature resistant and glass corrosion-resistant alloy according to claim 1 or 2, wherein, The Ni content is ≥ 58% by total weight of the alloy.
4. The method for preparing the high-temperature resistant and glass corrosion-resistant alloy according to any one of claims 1-3, characterized in that, The preparation method includes the following steps: S1: The raw material of element C, metal Ni, metal Cr and metal Fe are mixed and vacuum induction melting and refining are carried out to obtain refined material; after the refining is completed, the refined material is mixed and melted with metal Al, metal Ti, metal Y, metal Mn and elemental Si under protective gas, and then cast to obtain master alloy ingot. S2: Electroslag remelting of the master alloy ingot under a protective gas to obtain an electroslag remelted ingot; S3: The electroslag remelting ingot is homogenized to obtain a homogenized ingot; S4: The homogenized ingot is subjected to forging blanking and forging processing to obtain a forging; S5: The forging is subjected to solution treatment and aging treatment in sequence to obtain the high temperature resistant and glass corrosion resistant alloy.
5. The method for preparing the high-temperature resistant and glass corrosion-resistant alloy according to claim 4, wherein, The raw material for element C is at least one of graphite rods, graphite blocks, and graphite powder. The operating conditions for vacuum induction melting include: melting temperature of 1500-1600℃ and vacuum degree of 0.1-1Pa; The refining temperature is 1450-1500℃, and the refining time is 10-20 minutes; The mixing and melting temperature is 1500-1600℃, and the mixing and melting time is 3-6 minutes; The pouring temperature is 1450-1500℃.
6. The method for preparing the high-temperature resistant and glass corrosion-resistant alloy according to claim 4, wherein, The electroslag remelting includes spreading electro-slag for arc initiation and melting, and the electro-slag comprises, by weight, 20-25% Al2O3, 20-30% CaO, 4-6% TiO2, 1-4% MgO, 40-60% CaF2, and 0-1% SiO2.
7. The method for preparing the high-temperature resistant and glass corrosion-resistant alloy according to claim 4, wherein, The homogenization treatment is performed at a temperature of 1150-1200℃ for a duration of >6 hours.
8. The method for preparing the high-temperature resistant and glass corrosion-resistant alloy according to claim 4, wherein, The final forging temperature of the forging billet and the final forging temperature of the forging process are each independently ≥950℃; The forging ratio of the forging process is 2-5.
9. The method for preparing the high-temperature resistant and glass corrosion-resistant alloy according to claim 4, wherein, The solution treatment temperature is 1050-1090℃, and the solution treatment time is 10-30 min; The aging treatment temperature is 700-720℃, and the aging treatment time is 5-20h.
10. The application of the high-temperature resistant and glass corrosion resistant alloy according to any one of claims 1-3 or the high-temperature resistant and glass corrosion resistant alloy prepared by the preparation method according to any one of claims 4-9 in the preparation of electrodes for nuclear waste glass solidification furnaces.
Citation Information
Patent Citations
Anti-vibration alloy material for nuclear power station steam generator and preparation process thereof
CN102732751A
Fused salt corrosion resistant nickel-based deformable high-temperature alloy and preparation method thereof
CN105112727A